PENGARUH LATIHAN BERLARI ZIG-ZAG MELEWATI CONE MENGGUNAKAN BOLA TERHADAP KEMAMPUAN DRIBBLING PEMAIN SSB UNRI - Randa Saputra Alcahyadi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations in the field it is known that there are many deficiencies that occur in the Unri Pekanbaru SSB Team influenced by technical factors, such as dribbling. Many athletes who, when dribbling too far away from their feet and are not supported by a zig-zag run that looks stiff, makes it easy for the opponent to grab the ball, this has an impact on the team's appearance. pretest dribbling test (Marjohan, 2004: 145), After that the sample was given a training program Running Zig-Zag Through Cone Using the Ball for 16 meetings. After that, the Posttest dribbling test is done. The data obtained were analyzed descriptively, then further testing of the research hypotheses that had been submitted was according to the problem, namely: